TANTANGAN DAN PELUANG DALAM PENERAPAN AKUNTANSI MANAJEMEN BERKELANJUTAN DI NEGARA BERKEMBANG - Firdaus; Dwi Astono, Ari; Nurhayati, Nurhayati; Jatmiko, M Roby; Sitti Nurrahmah, Wa Ode; Sulistiyaningsih, Sri; Hendriyanto, Asepta; Mulyanto, Kukuh; Ismanto, Fiderius; Effendi, Meizar (Jurnal Akuntansi dan Bisnis, 2024)
The implementation of Sustainable Management Accounting (SMA) in developing nations is examined in this paper along with its prospects and obstacles. To achieve long-term sustainability, SMA incorporates social, economic, and environmental factors into business decision-making. SMA adoption in underdeveloped nations is hampered by issues like a lack of funding, a lack of environmental consciousness, and a lack of training and technology. SMA does, however, also have a number of noteworthy advantages, including increased operational effectiveness, better risk management, and higher standing in a global marketplace that is becoming more and more concerned with sustainability. This study examines the challenges and tactics in implementing SMA using a qualitative methodology and case studies of businesses in underdeveloped nations. It is anticipated that the results will help businesses and policymakers create and implement SMA in a way that promotes social, economic, and environmental sustainability.